Transformation Towards Sustainability: A Novel Interdisciplinary Framework from RWTH Aachen University - Letmathe, Peter; Roll, Christine; Balleer, Almut; Böschen, Stefan; Breuer, Wolfgang; Förster, Agnes; Gramelsberger, Gabriele; Greiff, Kathrin; Häußling, Roger; Lemme, Max (Springer Nature, 2024)
The global environmental crisis, technological developments, the COVID-19 pandemic, and ongoing economic and political globalization are just a few of the developments that are massively increasing the pressure for transformation on regions, companies and society as a whole. In addition, the digital age is accelerating transformation processes that are already underway. This contributed book addresses these developments and presents a new framework for transformation research and practice that has been developed and already validated by researchers of the RWTH Aachen University. The RWTH way includes inter- and transdisciplinary approaches from many disciplines, looking at technological and societal change from different perspectives. A distinction is made between analysis, i.e., research on transformation processes, impact, i.e., transformational research, and change in research itself, i.e. research transformation. The book not only creates a new understanding of transformation research, but also provides actionable impulses for scholars and practitioners in many fields. This is an open access book.